VARIATION IN THE FORMATION OF SOME BIOMOLECULES IN CABBAGE (BRASSICA OLERACEA L. VAR CAPITATA) LEAF INDUCED BY ENDOSULFAN - MANZOOR A. ASHRAFI; GOUTAM K. PANDIT (The Bioscan, 2015)
Synthetic pesticides, used to control the pests of various crops, have an effect in the quantitative formation of their biomolecules as well. The present experiment was carried out to study the effect of different doses (control, T1: 0; recommended, T2: 0.844 L ha–1 and double of recommended, T3: 1.688 L ha–1) of endosulfan on the formation of carbohydrate, total free amino acid, protein, total phenol and total chlorophyll contents of cabbage leaf on 1, 7, 14, 21, 28 and 35 days after application (DAA). In comparison with 1st DAA, the carbohydrate content decreased to 6.20 and 5.29% for T2 and T3 doses respectively on 35th DAA with no change in control. The total free amino acid content increased to the extent of 110.21, 92.87 and 99.79% and the protein content decreased to 57.37, 30.72 and 37.11% as recorded on 35th DAA in case of T1, T2 and T3 doses respectively. The total phenol level increased to 18.42, 27.65 and 35.33% for T1, T2 and T3 doses respectively on the last DAA. The total chlorophyll content was also found to increase to 25.64, 23.81 and 27.50% on 35th DAA in case of T1, T2 and T3 doses respectively with a decrease in midway. So the trend of formation of the studied biomolecules as observed in cabbage leaf due to endosulfan varied differently.